2020
DOI: 10.1183/16000617.0073-2019
|View full text |Cite
|
Sign up to set email alerts
|

α1-Antitrypsin deficiency and chronic respiratory disorders

Abstract: α1-antitrypsin deficiency (AATD) is a hereditary disorder associated with a risk of developing liver disease and pulmonary emphysema, and other chronic respiratory disorders (mainly asthma and bronchiectasis); Z variant is the commonest deficient variant of AAT. Determining AAT concentration in serum or plasma and identifying allelic variants by phenotyping or genotyping are fundamental in the diagnosis of AATD. Initial evaluation and annual follow-up measurement of lung function, including post-bronchodilator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 58 publications
1
35
0
1
Order By: Relevance
“…CD2, CD4, and CD8 can be cleaved on the surface of T-cells by ELANE and CTSG that dysregulate T-cell function [ 25 ]. It was reported that patients that lack alpha-1 antitrypsin (α1-Pi) which is the physiological inhibitor of PRTN3 and ELANE carries a high risk of developing emphysema [ 26 ]. Azurophil granules also carry Cathepsin D which was reported to be up-regulated in the pulmonary macrophages in a mouse model of cigarette smoking [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD2, CD4, and CD8 can be cleaved on the surface of T-cells by ELANE and CTSG that dysregulate T-cell function [ 25 ]. It was reported that patients that lack alpha-1 antitrypsin (α1-Pi) which is the physiological inhibitor of PRTN3 and ELANE carries a high risk of developing emphysema [ 26 ]. Azurophil granules also carry Cathepsin D which was reported to be up-regulated in the pulmonary macrophages in a mouse model of cigarette smoking [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD2, CD4, and CD8 can be cleaved on the surface of T-cells by ELANE and CTSG that dysregulate T-cell Function [29]. It was reported that patients that lack alpha-1 antitrypsin (α1-Pi) which s the physiological inhibitor of PRTN3 and ELANE carries a high risk of developing emphysema [30]. Azurophil granules also carry Cathepsin D which was reported to be up-regulated in the pulmonary macrophages in a mouse model of cigarette smoking [31].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating protein α 1 -antitrypsin (AAT) effectively inhibits proteases and also controls neutrophilic inflammation [14]. In the presence of AAT deficiency, augmentation therapy with i.v.…”
Section: Drugs That Antagonize Products Of the Cellular Components Of Inflammationmentioning
confidence: 99%
“…purified AAT becomes central. However, one of the main disadvantages of AAT therapy is that intravenous AAT arrives at the lung in a relatively inactive state [14]. To improve AAT replacement therapy, new intravenous formulations have been developed.…”
Section: Drugs That Antagonize Products Of the Cellular Components Of Inflammationmentioning
confidence: 99%